2006
DOI: 10.1634/stemcells.2006-0399
|View full text |Cite
|
Sign up to set email alerts
|

Neurosphere Assays: Growth Factors and Hormone Differences in Tumor and Nontumor Studies

Abstract: The "no new neuron" dogma that the brain is quiescent throughout adult life has been challenged by the discovery of cells with stem cell-like qualities of self-renewal and multipotency in the subventricular zone of the lateral ventricles and the dentate gyrus of the hippocampus in adults. This self-renewing capacity also makes these neural stem cells a possible source of brain tumors, which was supported by the discovery of self-sustaining brain tumor stem-like cells in cancers such as glioblastoma multiforme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 64 publications
(168 reference statements)
1
63
0
Order By: Relevance
“…Spheroid formation is commonly regarded as an indication of self-renewal and remains a standard for determining the presence of stem-like cells in both tumor and nontumor tissues. 11,31 In the current study, the presence of sarcospheres confirmed previous results showing stem-like cells are present in bone sarcomas. 3 The result is also consistent with the hypothesis proposed by Setoguchi et al 17 suggesting that cancer stem cells persist in many cell lines, even when they have been maintained for many years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Spheroid formation is commonly regarded as an indication of self-renewal and remains a standard for determining the presence of stem-like cells in both tumor and nontumor tissues. 11,31 In the current study, the presence of sarcospheres confirmed previous results showing stem-like cells are present in bone sarcomas. 3 The result is also consistent with the hypothesis proposed by Setoguchi et al 17 suggesting that cancer stem cells persist in many cell lines, even when they have been maintained for many years.…”
Section: Discussionsupporting
confidence: 92%
“…We examined four human osteosarcoma cell lines for their ability to form spherical clones (sarcospheres) as an indicator of stem cell self-renewal. 31 At near confluence, we dissociated these monolayer cultures into single-cell suspensions and inoculated them into a serum-free medium at a clonogenic density of 60,000 cells/ well in low-adhesive six-well plates. After seven to ten days, all four human osteosarcoma cells were able to form a sarcosphere, a hallmark of stem cell self-renewal.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33][34] Neurosphere in RB cells is an indicator of self-renewal and cycling in the stem cells, especially Y79 and WERI-Rb1. 35 IRB-1 showed the capacity to form neurospheres, an indicator of stem cell self-renewal. 35 IRB-1 Cells derived from primary RB tumor could be used as a model for cancer research including for genomic and transcription analysis and evaluation of different treatment protocols for RB.…”
Section: Chromosome Studiesmentioning
confidence: 99%
“…35 IRB-1 showed the capacity to form neurospheres, an indicator of stem cell self-renewal. 35 IRB-1 Cells derived from primary RB tumor could be used as a model for cancer research including for genomic and transcription analysis and evaluation of different treatment protocols for RB. The main limitation of this study is the inability to make genetic study over IRB-1 cells at the time.…”
Section: Chromosome Studiesmentioning
confidence: 99%
“…A current paucity of stem cell markers for many tissue lineages prevents geneology tracing to determine the cellular origin of cancer stem cells, making the functional in vivo self-renewal assay the most reliable currently available (Clarke et al, 2006). Tumor sphere formation, such as neurospheres for BTSCs, provides a powerful tool for the study of cancer stem cell self-renewal in culture, but care must be taken in the interpretation of these results because the in vitro assay may or may not be selecting the cancer stem cells (Clarke et al, 2006) and is a phenomenon that does not occur in vivo (Chaichana et al, 2006). Even the term tumor initiating cell can lead to confusion, as cancer stem cells may not actually initiate tumors but be stimulated to neoplastic transformation by environmental insults (Clarke et al, 2006).…”
Section: Brain Tumors Contain a Distinct "Stem Cell" Populationmentioning
confidence: 99%